Catalogue and historical overview of juvenile instars of oribatid mites (Acari: Oribatida) - Norton, Roy A.; Ermilov, Sergey G. (Zootaxa, 2014)
Oribatid mites (Acari: Oribatida) comprise a taxonomically and morphologically diverse suborder of about 10,000 described species, not including the hyporder Astigmata, with collectively a global distribution. They are primarily soil and litter inhabitants, feeding on fungi and decaying plant remains with various levels of specificity. Though all five active instars are important for reasons that relate to both ecology and systematics, most species are known only as adults. Our purpose was to gather the existing world literature on the active juvenile instars (i.e., excluding prelarva) of oribatid mites, to put classifications and nomenclature in a current context, and to identify the nature of the information in each paper. A selected historical overview identifies the contributions of 19th century authors C.L. Koch, H. Nicolet and A.D. Michael, and summarizes errors that resulted in various oribatid mite juveniles being classified in genera, families and even suborders that were different from those of their adult instars. The catalogue includes all species known to us for which juveniles have been described: 805 species in 310 genera, representing only about 8% of the known oribatid mite species and 30% of genera. These represent 118 families, about 70% of those known. At the superfamily level, representation is weakest among the diverse Oppioidea and Oribatuloidea, and those superfamilies with juveniles that are endophagous in organic substrates, such as Phthiracaroidea, Euphthiracaroidea and Carabodoidea. Representation is strongest in the middle-derivative hyporder Nothrina, in which adults and juveniles are more easily associated, and in brachypyline superfamilies that are mostly affiliated with aquatic, semiaquatic or intertidal environments, such as Limnozetoidea and Ameronothroidea. Juvenile instars remain unknown for 45 families of Brachypylina.          Four new nomenclatural actions were proposed: Ojaithrus nymphoides Habeeb, 1982 is a junior synonym of Hydrozetes californiensis Habeeb, 1974, Cepheus feideri Suciu & Panu, 1972 is a junior synonym of Conoppia palmicincta (Michael, 1880). Two species are recombined: Ceratozetes kirgisicus (Shaldybina, 1970) comb. nov. (from Ceratozetella); Scheloribates (Hemileius) nicki (Denmark & Woodring, 1965) comb. nov. (from Hemileius).